PENGARUH KUALITAS INFORMASI DAN KEMUDAHAN TRANSAKSI TERHADAP KEPUASAN KONSUMEN SERTA DAMPAKNYA PADA LOYALITAS KONSUMEN DALAM BERBELANJA FASHION ONLINE DI BANDA ACEH - Safrika Safrika (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2019)
This research aims to effects the influence of the quality of information and ease of discounted rates on consumer satisfaction and its impact on customer loyalty in shopping online fashion products in Banda Aceh. Research samples as much as 120 people of Banda Aceh which is consumers who never shop online. The collection of data using questionnaires and then analyzed with data using statistics structural equition equipment models (SEM) with this method of Partial Square (PLS). Studies have found that the quality of information and ease of discounted rates affect customer satisfaction and loyalty in shopping fashion online in Banda Aceh. Consumer satisfaction affect customer loyalty. Quality of information and ease of discounted rates affect customer loyalty in shopping fashion online in Banda Aceh through consumer satisfaction. The influence of the direct effect) both variables to customer loyalty was considered significant. Then the influence of the direct effect of consumer satisfaction toward consumer loyality is also significant. Thus it can be concluded that consumer satisfaction can serve as an intermediary variable (intervening variables) between consumer satisfaction in one side with the quality of information and ease of discounted rates on the other side Key Words : Loyalits Consumers, consumer satisfaction, quality of information and ease of transaction.